2010
DOI: 10.1073/pnas.0914991107
|View full text |Cite
|
Sign up to set email alerts
|

High frequency targeted mutagenesis in Arabidopsis thaliana using zinc finger nucleases

Abstract: We report here an efficient method for targeted mutagenesis of Arabidopsis genes through regulated expression of zinc finger nucleases (ZFNs)-enzymes engineered to create DNA doublestrand breaks at specific target loci. ZFNs recognizing the Arabidopsis ADH1 and TT4 genes were made by Oligomerized Pool ENgineering (OPEN)-a publicly available, selection-based platform that yields high quality zinc finger arrays. The ADH1 and TT4 ZFNs were placed under control of an estrogen-inducible promoter and introduced into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
236
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 341 publications
(244 citation statements)
references
References 49 publications
5
236
0
3
Order By: Relevance
“…In previous studies, HR-mediated gene-replacement strategies have been the preferred mode of gene replacement in plants (Wright et al, 2005;Shukla et al, 2009;Townsend et al, 2009;de Pater et al, 2013), while NHEJ-mediated repair of ZFN-induced DSBs has been limited to targeted mutagenesis and transgene removal (Lloyd et al, 2005;Morton et al, 2006;Maeder et al, 2008;de Pater et al, 2009;Tovkach et al, 2009;Osakabe et al, 2010;Petolino et al, 2010;Zhang et al, 2010). Our findings show that the NHEJ DNA-repair pathway can be harnessed for gene replacement in plant species.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In previous studies, HR-mediated gene-replacement strategies have been the preferred mode of gene replacement in plants (Wright et al, 2005;Shukla et al, 2009;Townsend et al, 2009;de Pater et al, 2013), while NHEJ-mediated repair of ZFN-induced DSBs has been limited to targeted mutagenesis and transgene removal (Lloyd et al, 2005;Morton et al, 2006;Maeder et al, 2008;de Pater et al, 2009;Tovkach et al, 2009;Osakabe et al, 2010;Petolino et al, 2010;Zhang et al, 2010). Our findings show that the NHEJ DNA-repair pathway can be harnessed for gene replacement in plant species.…”
Section: Discussionmentioning
confidence: 92%
“…However, it is important to note that while ZFNinduced DSBs can indeed induce the HR repair machinery, most of these breaks are repaired by the cell's NHEJ DNA-repair machinery in plant and other species. Thus, ZFNs have also been used for the induction of site-specific mutagenesis in many eukaryotic cells, including plant cells (Lloyd et al, 2005;Tovkach et al, 2009;Marton et al, 2010;Osakabe et al, 2010;Zhang et al, 2010;Curtin et al, 2011;Even-Faitelson et al, 2011). More recently, ZFNs have been used for NHEJmediated targeted chromosomal deletions (Lee et al, 2010;Söllü et al, 2010), transgene removal (Petolino et al, 2010), and even NHEJ-mediated targeted DNA integration in mammalian genomes (Orlando et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most obvious application of such an approach is the use of artificially constructed modular endonucleases, such as meganucleases (26), zinc finger nucleases (27), or transcription activator-like effector nucleases (28), that are designed to cut at a specific site in the gene of interest. Recent studies demonstrated that the aforementioned nucleases can be applied in the same way as I-SceI used in our study for different DSB-induced recombination reactions in plants (8,15,19,29).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to be able to obtain targeted mutations and to design new mutants using zinc finger nucleases and novel means in plants for functional characterization ( Fig. 2; Zhang et al, 2010).…”
Section: Integrative Approaches For Future Discoverymentioning
confidence: 99%